Evaluation of land uses on the global occurrence of vadose zone nitrate - Hanamant M. Halli; Chittaranjan Ray; Somdipta Bagchi; Daniel D. Snow; Arindam Malakar (Groundwater for Sustainable Development, 2026)

Relations of residential greenness with immunity and inflammation - Daniel W. Riggs; Sonia Cobbold; Clara G. Sears; Marina V. Malovichko; Israel Sithu; Brian E. Sansbury; Ray Yeager; Marcin Wysoczynski; Sanjay Srivastava; Rachel J. Keith; Aruni Bhatnagar (Environmental Research, 2026)

A data-driven dynamic modeling of fish-like robot enabled by artificial neural network - Qilong Zhong; Xianle Zeng; Morel Groper; Daniel Q Tan; Ray Wai Man Kong; Mingyi Liu (Ocean Engineering, 2026)

Long-Term Remediation of the Savage River Mine Using Local Neutralising Waste Rock and Novel Flow-Through Waste Storage Facilities - Andrea R. Gerson; Stephen Kent; Bruce Hutchison; Daniel Ray; Roger St.C. Smart; Tony Ferguson (Mine Water and the Environment, 2026)

Evaluation of the effects of hybrids of metronidazole and eugenol analogues as inhibitors of the Staphylococcus aureus NorA efflux pump: an in vitro and in silico analysis - Lucas dos Santos Sa; João Arthur de Oliveira Borges; Francisco Ruan Moreira da Silva Santos; Cicera Laura Roque Paulo; Daniel Sampaio Alves; Ewerton Yago de Sousa Rodrigues; Ray Silva de Almeida; Sheila Alves Gonçalves; Cícera Datiane de Morais Oliveira Tintino; Lucas Lopardi Franco; Ana Laura Marques Trinca; Douglas Henriques Novais; et al. (Folia Microbiologica, 2026)
Staphylococcus aureus is a Gram-positive coccus-type bacterium responsible for colonizing various sites of the host’s body, thus generating several pathologies such as pneumonia, osteomyelitis, endocarditis, and even cases of sepsis. Eugenol, dihydroeugenol, guaiacol, and phenol are phenolic compounds with antimicrobial activities, as is the drug metronidazole; therefore, eight substances were synthesized by coupling metronidazole with the molecules mentioned above, thus originating the compounds AD1–AD8. The present study aimed to evaluate the antibacterial activity and the capacity of the compounds AD1–AD8 to amplify the action of norfloxacin and ethidium bromide against the S . aureus 1199B strain through the inhibition of the NorA efflux pump. Broth microdilution assays were performed to determine the MIC and to analyze the association of the compounds AD1–AD8 with norfloxacin and ethidium bromide, along with the membrane permeability test and molecular docking. The compounds AD1–AD8 obtained positive results as they exhibited a potentiating effect by reducing the MIC of norfloxacin and ethidium bromide against 1199B, thus evidencing interference with the functioning of the NorA efflux pump, which had already been predicted by the data obtained from the molecular docking assay, in addition to having demonstrated significant effects by acting on the S. aureus membrane. The information obtained from this research is in line with what is reported in the literature regarding the effects observed with eugenol, dihydroeugenol, and guaiacol and their derivatives when combined with other antibiotics against S. aureus strains that possess efflux pumps, with competitive inhibition being observed, as well as the possibility that the reduction in MIC may have occurred due to a reduction in gene expression levels. Further assays are needed to evaluate these possibilities. Based on the presented data, it was found that the compounds AD1–AD8 exhibit promising aspects to act as antibiotic adjuvants.

Transformation of inorganic reactive nitrogen species in a simulated vadose zone - Yvon Ukwishaka; Daniel N. Miller; Preetismita Borah; Daniel D. Snow; Michael Kaiser; Chittaranjan Ray; David Fleisher; Dennis Timlin; Vangimalla Reddy; Arindam Malakar (Science of The Total Environment, 2026)

Tuning the morphology of aerosolised cellulose nanocrystal particulates via controlled aggregation - Daniel Warnes; Wenyang Xu; Jia Hui Lim; Richard M. Parker; Bruno Frka-Petesic; Ray Freshwater; Camila Honorato-Rios; Yu Ogawa; Chiara Giorio; Silvia Vignolini (Carbohydrate Polymers, 2026)

Evaluating the performance of selected CMIP6 GCMs for simulations of historical temperature over Ethiopia - Alehegn Belay Tagele; Temesgen Gashaw Tarkegn; Pieter R. van Oel; Ram Lakhan Ray; Gebrekidan Worku Tefera; Sintayehu Fetene Demessie; Alemayehu Abate Shawul; Othoo Calvince Ouko; Daniel Berhanu; Amare Haileslassie; Abeyou W. Worqlul; Amare Bantider; et al. (Theoretical and Applied Climatology, 2026)
This study evaluates the performance of seven Global Climate Models (GCMs) from the Coupled Model Intercomparison Project Phase 6 (CMIP6) and their Ensemble mean in reproducing historical maximum (Tmax) and minimum (Tmin) temperatures across five agro-ecological zones (AEZs) of Ethiopia during 1995–2014. The assessment covers daily to annual time scales using observational and GCM datasets. Model performance was evaluated using Percent Bias (PBIAS), Root Mean Square Error (RMSE), and correlation coefficient (r), while the Comprehensive Rating Index (CRI) was applied for ranking. Results show substantial spatial and temporal variability in model performance. For Tmax, the Ensemble mean and EC-Earth3-veg performed best at the daily scale, while EC-Earth3-veg, MPI-ESM1-2-LR and BCC-CSM2-MR excelled at the monthly scale across most AEZs. Seasonally, top-performing models included Ensemble mean, MPI-ESM1-2-LR and MRI-ESM2-0 during Bega (October-January), EC-Earth3-veg, CNRM-CM6-1 and Ensemble mean during Belg (February-May) and CNRM-CM6-1 and MPI-ESM1-2-LR during Kiremt (June-September). For Tmin, CNRM-CM6-1, BCC-CSM2-MR and Ensemble mean ranked highest at both daily and monthly scales in most AEZs. At the annual scale, MRI-ESM2-0, Ensemble mean, MPI-ESM1-2-LR and CNRM-CM6-1 excel for Tmax, while EC-Earth3-veg, BCC-CSM2-MR and Ensemble mean lead for Tmin across most AEZs. MIROC6 consistently exhibited the weakest performance for both Tmax and Tmin across most AEZs and time periods. Thus, the Ensemble mean of all evaluated models does not consistently rank among the top three performers across all AEZs and time scales. The identified best-performing CMIP6 models provide valuable tools for assessing climate change impacts and developing region-and time-specific adaptation strategies in Ethiopia. Given the variability in GCM performance across AEZs and time scales, national or large-scale studies would benefit from using the Ensemble mean derived from the best-performing models. This study provides crucial insights into the strengths and weaknesses of different GCMs, supporting evidence-based decision-making and enhancing efforts to build climate resilience and adaptation strategies in the region.

Integrated in Vitro, in Vivo, Molecular Docking, and ADMET in Silico Assessment of β-Caryophyllene as a NorA Efflux Pump inhibitor in Resistant Staphylococcus Aureus (MRSA) - José Weverton Almeida-Bezerra; José Thyálisson da Costa Silva; Cícera Datiane de Morais Oliveira-Tintino; Adrielle Rodrigues Costa; Viviane Bezerra da Silva; Maria Flaviana Bezerra Morais-Braga; Irwin Rose Alencar de Menezes; Ana Carolina Ferreira Araujo; Lucas Yure Santos da Silva; Daniel Sampaio Alves; Guilherme Fernandes Teixeira; Lucas dos Santos Sa; et al. (Current Microbiology, 2026)

When does spillover from marine protected areas indicate benefits to fish abundance and catch? - Ray Hilborn; Mark Fitchett; John Hampton; Daniel Ovando (Theoretical Ecology, 2025)

Network of networks: Time series clustering of AmeriFlux sites - David E Reed; Housen Chu; Brad G. Peter; Jiquan Chen; Michael Abraha; Brian Amiro; Ray G. Anderson; M. Altaf Arain; Paulo Arruda; Greg A. Barron-Gafford; Carl Bernacchi; Daniel P. Beverly; et al. (Agricultural and Forest Meteorology, 2025)

Comparing voluntary and government-mandated management measures for meeting sustainable fishing targets - Michael C. Melnychuk; Samantha Lees; Pedro Veiga; Jennifer Rasal; Nicole Baker; Lauren Koerner; Daniel Hively; Hiroyuki Kurota; Carryn L. de Moor; Maite Pons; Pamela M. Mace; Ana M. Parma; et al. (Journal of Environmental Management, 2025)

Intra-neighborhood associations between residential greenness and blood pressure - Ray Yeager; Rachel J. Keith; Daniel W. Riggs; Daniel Fleischer; Matthew H.E.M. Browning; Alessandro Ossola; Kandi L. Walker; Joy L. Hart; Sanjay Srivastava; Shesh N. Rai; Ted Smith; Aruni Bhatnagar (Science of The Total Environment, 2024)

Sources of per- and polyfluoroalkyl substances in an arid, urban, wastewater-dominated watershed - Kyle A. Thompson; Hannah Ray; Daniel Gerrity; Oscar Quiñones; Eric Dano; James Prieur; Brett Vanderford; Eva Steinle-Darling; Eric R.V. Dickenson (Science of The Total Environment, 2024)

Investigating the acidophilic microbial community's adaptation for enhancement indium bioleaching from high pulp density shredded discarded LCD panels - Andra Constantin; Fatemeh Pourhossein; Daniel Ray; Sebastien Farnaud (Journal of Environmental Management, 2024)

Mixed-Method Heat Acclimation Induces Heat Adaptations in International Triathletes Without Training Modification - Carl A. James; Ashley G. B. Willmott; C. W. Daniel Lee; T. K. Gabriel Pun; Ray Tai; Oliver R. Gibson (Journal of Science in Sport and Exercise, 2024)
Purpose Heat acclimation (HA) kinetics often necessitates that the intervention is conducted in the weeks immediately preceding athletic competitions, potentially interfering with a training taper. Therefore, we investigated the efficacy of a mixed-method HA protocol, superimposed over planned external training loads, during the 3-weeks prior to the 2022 U23 World Triathlon Championships. Methods Six international triathletes completed 8 pre-competition HA sessions (5 active: running/cycling, 3 passive: hot water immersion [HWI]), across 2-weeks. Outdoor high-intensity training sessions were followed by 30–60 min HWI, whilst low-intensity cycling/running sessions were completed in a hot, humid environmental chamber. To assess heat adaptations, participants completed three 25 min heat stress tests (HST) involving iso-speed treadmill running (session 1 = HST1, session 5 = HST2, and session 8 = HST3). Physiological, haematological and wellbeing monitoring were conducted throughout HA. Results Reduced heart rate (~ − 6 beats/min) was observed within HST3 ( P = 0.01, η p 2 = 0.64), versus HST1 and HST2. No changes in core temperature were observed across HSTs ( P = 0.055 , η p 2 = 0.44). Sweat sodium concentration was lower by HST2 at the arm (− 23 ± 16 mmol/L, P = 0.02) and back (− 27 ± 17 mmol/L, P = 0.01). White blood cell count reduced from baseline to the end of HA ( P = 0.02, η p 2 = 0.27), but no changes were found in any other haematological markers (all P > 0.05). Perceptual wellbeing measures did not change across HA (all P > 0.05). Conclusion By HST3, seven prior mixed-method HA sessions improved markers of heat adaptation (exercising HR and sweat concentration) within international triathletes. Mixed-method HA may be implemented without modifying training load, with no apparent detrimental effects on athlete health or training stress markers.

Reconstructing 120 years of climate change impacts on Joshua tree flowering - Jeremy B. Yoder; Ana Karina Andrade; Lesley A. DeFalco; Todd C. Esque; Colin J. Carlson; Daniel F. Shryock; Ray Yeager; Christopher I. Smith (Ecology Letters, 2024)
Quantifying how global change impacts wild populations remains challenging, especially for species poorly represented by systematic datasets. Here, we infer climate change effects on masting by Joshua trees ( Yucca brevifolia and Y. jaegeriana ), keystone perennials of the Mojave Desert, from 15 years of crowdsourced observations. We annotated phenophase in 10,212 geo‐referenced images of Joshua trees on the iNaturalist crowdsourcing platform, and used them to train machine learning models predicting flowering from annual weather records. Hindcasting to 1900 with a trained model successfully recovers flowering events in independent historical records and reveals a slightly rising frequency of conditions supporting flowering since the early 20th Century. This reflects increased variation in annual precipitation, which drives masting events in wet years—but also increasing temperatures and drought stress, which may have net negative impacts on recruitment. Our findings reaffirm the value of crowdsourcing for understanding climate change impacts on biodiversity.

Effects of increasing soil moisture on Antarctic desert microbial ecosystems - Eden Zhang; Sin Yin Wong; Paul Czechowski; Aleks Terauds; Angelique E. Ray; Nicole Benaud; Devan S. Chelliah; Daniel Wilkins; Kate Montgomery; Belinda C. Ferrari (Conservation Biology, 2024)
Overgeneralization and a lack of baseline data for microorganisms in high‐latitude environments have restricted the understanding of the microbial response to climate change, which is needed to establish Antarctic conservation frameworks. To bridge this gap, we examined over 17,000 sequence variants of bacteria and microeukarya across the hyperarid Vestfold Hills and Windmill Islands regions of eastern Antarctica. Using an extended gradient forest model, we quantified multispecies response to variations along 79 edaphic gradients to explore the effects of change and wind‐driven dispersal on community dynamics under projected warming trends. We also analyzed a second set of soil community data from the Windmill Islands to test our predictions of major environmental tipping points. Soil moisture was the most robust predictor for shaping the regional soil microbiome; the highest rates of compositional turnover occurred at 10–12% soil moisture threshold for photoautotrophs, such as Cyanobacteria , Chlorophyta , and Ochrophyta . Dust profiles revealed a high dispersal propensity for Chlamydomonas , a microalga, and higher biomass was detected at trafficked research stations. This could signal the potential for algal blooms and increased nonendemic species dispersal as human activities increase in the region. Predicted increases in moisture availability on the Windmill Islands were accompanied by high photoautotroph abundances. Abundances of rare oligotrophic taxa, such as Eremiobacterota and Candidatus Dormibacterota, which play a crucial role in atmospheric chemosynthesis, declined over time. That photosynthetic taxa increased as soil moisture increased under a warming scenario suggests the potential for competition between primary production strategies and thus a more biotically driven ecosystem should the climate become milder. Better understanding of environmental triggers will aid conservation efforts, and it is crucial that long‐term monitoring of our study sites be established for the protection of Antarctic desert ecosystems. Furthermore, the successful implementation of an improved gradient forest model presents an exciting opportunity to broaden its use on microbial systems globally.

Single-crystal 40Ar/39Ar dating of the Montagna Grande-Monte Gibele trachytic shield volcano, Pantelleria (Strait of Sicily rift zone), Italy - John C. White; Daniel P. Miggins; Ray Macdonald (Geochemistry, 2024)

Does urbanisation lead to parallel demographic shifts across the world in a cosmopolitan plant? - Aude E. Caizergues; James S. Santangelo; Rob W. Ness; Fabio Angeoletto; Daniel N. Anstett; Julia Anstett; Fernanda Baena‐Diaz; Elizabeth J. Carlen; Jaime A. Chaves; Mattheau S. Comerford; Karen Dyson; Mohsen Falahati‐Anbaran; et al. (Molecular Ecology, 2024)
Urbanisation is occurring globally, leading to dramatic environmental changes that are altering the ecology and evolution of species. In particular, the expansion of human infrastructure and the loss and fragmentation of natural habitats in cities is predicted to increase genetic drift and reduce gene flow by reducing the size and connectivity of populations. Alternatively, the ‘urban facilitation model’ suggests that some species will have greater gene flow into and within cities leading to higher diversity and lower differentiation in urban populations. These alternative hypotheses have not been contrasted across multiple cities. Here, we used the genomic data from the GLobal Urban Evolution project (GLUE), to study the effects of urbanisation on non‐adaptive evolutionary processes of white clover ( Trifolium repens ) at a global scale. We found that white clover populations presented high genetic diversity and no evidence of reduced N e linked to urbanisation. On the contrary, we found that urban populations were less likely to experience a recent decrease in effective population size than rural ones. In addition, we found little genetic structure among populations both globally and between urban and rural populations, which showed extensive gene flow between habitats. Interestingly, white clover displayed overall higher gene flow within urban areas than within rural habitats. Our study provides the largest comprehensive test of the demographic effects of urbanisation. Our results contrast with the common perception that heavily altered and fragmented urban environments will reduce the effective population size and genetic diversity of populations and contribute to their isolation.

HydroShare retrospective: Science and technology advances of a comprehensive data and model publication environment for the water science domain - David G. Tarboton; Daniel P. Ames; Jeffery S. Horsburgh; Jonathan L. Goodall; Alva Couch; Richard Hooper; Jerad Bales; Shaowen Wang; Anthony Castronova; Martin Seul; Ray Idaszak; Zhiyu Li; et al. (Environmental Modelling & Software, 2024)

Interplay of legacy irrigation and nitrogen fertilizer inputs to spatial variability of arsenic and uranium within the deep vadose zone - Arindam Malakar; Chittaranjan Ray; Matteo D'Alessio; Jordan Shields; Craig Adams; Marty Stange; Karrie A. Weber; Daniel D. Snow (Science of The Total Environment, 2023)

Importance of snowmelt on soil nitrate leaching to groundwater – A model study - Sahila Beegum; Arindam Malakar; Chittaranjan Ray; Daniel D. Snow (Journal of Contaminant Hydrology, 2023)

Consensus Head Acceleration Measurement Practices (CHAMP): Laboratory Validation of Wearable Head Kinematic Devices - Lee Gabler; Declan Patton; Mark Begonia; Ray Daniel; Ahmad Rezaei; Colin Huber; Gunter Siegmund; Tyler Rooks; Lyndia Wu (Annals of Biomedical Engineering, 2022)
Wearable devices are increasingly used to measure real-world head impacts and study brain injury mechanisms. These devices must undergo validation testing to ensure they provide reliable and accurate information for head impact sensing, and controlled laboratory testing should be the first step of validation. Past validation studies have applied varying methodologies, and some devices have been deployed for on-field use without validation. This paper presents best practices recommendations for validating wearable head kinematic devices in the laboratory, with the goal of standardizing validation test methods and data reporting. Key considerations, recommended approaches, and specific considerations were developed for four main aspects of laboratory validation, including surrogate selection, test conditions, data collection, and data analysis. Recommendations were generated by a group with expertise in head kinematic sensing and laboratory validation methods and reviewed by a larger group to achieve consensus on best practices. We recommend that these best practices are followed by manufacturers, users, and reviewers to conduct and/or review laboratory validation of wearable devices, which is a minimum initial step prior to on-field validation and deployment. We anticipate that the best practices recommendations will lead to more rigorous validation of wearable head kinematic devices and higher accuracy in head impact data, which can subsequently advance brain injury research and management.

On-Field Deployment and Validation for Wearable Devices - Calvin Kuo; Declan Patton; Tyler Rooks; Gregory Tierney; Andrew McIntosh; Robert Lynall; Amanda Esquivel; Ray Daniel; Thomas Kaminski; Jason Mihalik; Nate Dau; Jillian Urban (Annals of Biomedical Engineering, 2022)
Wearable sensors are an important tool in the study of head acceleration events and head impact injuries in sporting and military activities. Recent advances in sensor technology have improved our understanding of head kinematics during on-field activities; however, proper utilization and interpretation of data from wearable devices requires careful implementation of best practices. The objective of this paper is to summarize minimum requirements and best practices for on-field deployment of wearable devices for the measurement of head acceleration events in vivo to ensure data evaluated are representative of real events and limitations are accurately defined. Best practices covered in this document include the definition of a verified head acceleration event, data windowing, video verification, advanced post-processing techniques, and on-field logistics, as determined through review of the literature and expert opinion. Careful use of best practices, with accurate acknowledgement of limitations, will allow research teams to ensure data evaluated is representative of real events, will improve the robustness of head acceleration event exposure studies, and generally improve the quality and validity of research into head impact injuries.

Recent trends in abundance and fishing pressure of agency‐assessed small pelagic fish stocks - Ray Hilborn; Claudio C. Buratti; Erich Díaz Acuña; Daniel Hively; Jeppe Kolding; Hiroyuki Kurota; Nicole Baker; Pamela M. Mace; Carryn L. de Moor; Soyoka Muko; Giacomo Chato Osio; Ana M. Parma; et al. (Fish and Fisheries, 2022)
Small pelagic fishes are used for human consumption, fishmeal and fish oil. They constitute 25% of global fish catch and have been of considerable conservation concern because of their intermediate position in aquatic food webs, often being a dominant dietary component of marine predators. This paper provides an overview of trends in abundance and fishing pressure on small pelagic fish stocks from single‐species scientific assessments that constitute 60% of global small pelagic catch. While most individual stocks have exhibited wide variability in abundance (typical of small pelagics compared with other fish taxa), across stocks there has been remarkable stability in average fishing pressure and biomass since 1970. On average, since 1970, the biomass of assessed small pelagic stocks is estimated to have been slightly above the biomass that would produce maximum sustainable yield, but estimation of this quantity for highly fluctuating stocks is quite uncertain. There were significant differences among assessed regions, with the Mediterranean and Black Sea of greatest concern for high and growing fishing pressure. The 40% of global small pelagic fish catch not covered by single‐species quantitative stock assessments since 1970 comes largely from Asia, where catches have continued to increase. At regional levels, the average abundance of assessed small pelagic fish is largely unrelated to average fishing pressure, which we argue results both from the portfolio effect, where numerous stocks fluctuate with little correlation in abundance, and from the short life span of small pelagics coupled with recruitment largely independent of spawning abundance.

Testing the potential contribution of Wolbachia to speciation when cytoplasmic incompatibility becomes associated with host‐related reproductive isolation - Daniel J. Bruzzese; Hannes Schuler; Thomas M. Wolfe; Mary M. Glover; Joseph V. Mastroni; Meredith M. Doellman; Cheyenne Tait; Wee L. Yee; Juan Rull; Martin Aluja; Glen Ray Hood; Robert B. Goughnour; et al. (Molecular Ecology, 2022)
Endosymbiont‐induced cytoplasmic incompatibility (CI) may play an important role in arthropod speciation. However, whether CI consistently becomes associated or coupled with other host‐related forms of reproductive isolation (RI) to impede the transfer of endosymbionts between hybridizing populations and further the divergence process remains an open question. Here, we show that varying degrees of pre‐ and postmating RI exist among allopatric populations of two interbreeding cherry‐infesting tephritid fruit flies ( Rhagoletis cingulata and R . indifferens ) across North America. These flies display allochronic and sexual isolation among populations, as well as unidirectional reductions in egg hatch in hybrid crosses involving southwestern USA males. All populations are infected by a Wolbachia strain, w Cin2, whereas a second strain, w Cin3, only co‐infects flies from the southwest USA and Mexico. Strain w Cin3 is associated with a unique mitochondrial DNA haplotype and unidirectional postmating RI, implicating the strain as the cause of CI. When coupled with nonendosymbiont RI barriers, we estimate the strength of CI associated with w Cin3 would not prevent the strain from introgressing from infected southwestern to uninfected populations elsewhere in the USA if populations were to come into secondary contact and hybridize. In contrast, cytoplasmic–nuclear coupling may impede the transfer of w Cin3 if Mexican and USA populations were to come into contact. We discuss our results in the context of the general paucity of examples demonstrating stable Wolbachia hybrid zones and whether the spread of Wolbachia among taxa can be constrained in natural hybrid zones long enough for the endosymbiont to participate in speciation.

A history and evaluation of catch‐only stock assessment models - Daniel Ovando; Christopher M. Free; Olaf P. Jensen; Ray Hilborn (Fish and Fisheries, 2022)
Understanding the status of fish stocks is a critical step in ensuring the ecological and economic sustainability of marine ecosystems. However, at least half of global catch and a vast majority of global fisheries lack formal stock assessments, largely due to a lack of sufficient data. Catch data, loosely referring to any catch records be it inclusive of discards or not, are the only type of fishery data available across a wide range of fisheries at a global scale. This has given rise to a long list of so‐called “catch‐only” models, intended to estimate aspects of stock status based primarily on characteristics of a fishery's catch history. In this paper, we review the history, performance and potential of “catch‐only” models to estimate stock biomass status. While individual catch‐only models often report good performance, repeated efforts to examine the performance of these models have consistently found them to be imprecise and biased when applied to new data‐limited fisheries. We demonstrate that a large reason for this is the simple lack of information on stock status contained in the shape of a catch history alone. Off‐the‐shelf use of catch‐only models can lead to poor and biased estimates of stock status, potentially hindering efforts at effective management.

Area‐based management of blue water fisheries: Current knowledge and research needs - Ray Hilborn; Vera N. Agostini; Milani Chaloupka; Serge M. Garcia; Leah R. Gerber; Eric Gilman; Quentin Hanich; Amber Himes‐Cornell; Alistair J. Hobday; David Itano; Michel J. Kaiser; Hilario Murua; et al. (Fish and Fisheries, 2022)
The pelagic fisheries beyond the continental shelves are currently managed with a range of tools largely based on regulating effort or target catch. These tools comprise both static and dynamic area‐based approaches to include gear limitations, closed areas and bycatch limits. There are increasing calls for additional area‐based interventions, particularly expansion of marine protected areas, with many now advocating closing 30% of the oceans to fishing. In this paper, we review the objectives, methods and successes of area‐based management of blue water fisheries across objectives related to food production and environmental, social and economic impacts. We also consider the methods used to evaluate the performance of area‐based regulations and provide a summary of the relative quality of evidence from alternative evaluation approaches. We found that few area‐based approaches have been rigorously evaluated, and that it is often difficult to obtain requisite observational data to define a counterfactual to infer any causal effect for such evaluation. Management agencies have been relatively successful at maintaining important commercial species at or near their target abundance, but success at meeting ecological or social goals is less clear. The high mobility of both target and bycatch species generally reduces the effectiveness of area‐based management, and shifting distributions due to climate change suggest that adaptive rather than static approaches will be preferred. We prioritize research and management actions that would make area‐based management more effective.

Screening of cultivars for tissue culture response and establishment of genetic transformation in a high-yielding and disease-resistant cultivar of Theobroma cacao - Jesse Jones; Elaine Zhang; Dominick Tucker; Daniel Rietz; Douglas Dahlbeck; Michael Gomez; Claudia Garcia; Jean-Philippe Marelli; Donald Livingstone; Ray Schnell; Brian Staskawicz; Myeong-Je Cho (In Vitro Cellular & Developmental Biology - Plant, 2022)
A highly efficient transformation protocol is a prerequisite to developing genetically modified and genome-edited crops. A tissue culture system spanning culture initiation from floral material to conversion of embryos to plants has been tested and improved in Theobroma cacao . Nine cultivars were screened for their tissue culture response and susceptibility to Agrobacterium transfer-DNA delivery as measured through transient expression. These key factors were used to determine the genetic transformability of various cultivars. The high-yielding, disease-resistant cultivar INIAPG-038 was selected for stable transformation and the method was further optimized. Multiple transgenic events were produced using two vectors containing both yellow fluorescent protein and neomycin phosphotransferase II genes. A two-fold strategy to improve both T-DNA delivery and secondary somatic embryogenesis rates was conducted to improve overall transformation frequency. The use of Agrobacterium strain AGL1 and cotyledon tissue derived from secondary somatic embryos ranging in size between 4 to 10 mm resulted in the highest T-DNA delivery efficiency. Furthermore, the use of higher concentrations of basal salts and cupric sulfate in the medium increased the frequency of explants producing greater than ten embryos by five-fold and four-fold during secondary somatic embryogenesis, respectively. Consequently, an optimal combination of all these components resulted in a successful transformation of INIAPG-038 with 3.7% frequency at the T 0 plant-level. Grafting transgenic scions with undeveloped roots to non-transgenic seedlings with healthy roots helped make plantlets survive and facilitated quick transplantation to the soil. The presented strategy can be applied to improve tissue culture response and transformation frequency in other Theobroma cacao cultivars.

Common, low-frequency, rare, and ultra-rare coding variants contribute to COVID-19 severity - Chiara Fallerini; Nicola Picchiotti; Margherita Baldassarri; Kristina Zguro; Sergio Daga; Francesca Fava; Elisa Benetti; Sara Amitrano; Mirella Bruttini; Maria Palmieri; Susanna Croci; Mirjam Lista; et al. (Human Genetics, 2022)
The combined impact of common and rare exonic variants in COVID-19 host genetics is currently insufficiently understood. Here, common and rare variants from whole-exome sequencing data of about 4000 SARS-CoV-2-positive individuals were used to define an interpretable machine-learning model for predicting COVID-19 severity. First, variants were converted into separate sets of Boolean features, depending on the absence or the presence of variants in each gene. An ensemble of LASSO logistic regression models was used to identify the most informative Boolean features with respect to the genetic bases of severity. The Boolean features selected by these logistic models were combined into an Integrated PolyGenic Score that offers a synthetic and interpretable index for describing the contribution of host genetics in COVID-19 severity, as demonstrated through testing in several independent cohorts. Selected features belong to ultra-rare, rare, low-frequency, and common variants, including those in linkage disequilibrium with known GWAS loci. Noteworthily, around one quarter of the selected genes are sex-specific. Pathway analysis of the selected genes associated with COVID-19 severity reflected the multi-organ nature of the disease. The proposed model might provide useful information for developing diagnostics and therapeutics, while also being able to guide bedside disease management.

Assessing the population‐level conservation effects of marine protected areas - Daniel Ovando; Jennifer E. Caselle; Christopher Costello; Olivier Deschenes; Steven D. Gaines; Ray Hilborn; Owen Liu (Conservation Biology, 2021)
Marine protected areas (MPAs) cover 3–7% of the world's ocean, and international organizations call for 30% coverage by 2030. Although numerous studies show that MPAs produce conservation benefits inside their borders, many MPAs are also justified on the grounds that they confer conservation benefits to the connected populations that span beyond their borders. A network of MPAs covering roughly 20% of the Channel Islands National Marine Sanctuary was established in 2003, with a goal of providing regional conservation and fishery benefits. We used a spatially explicit bioeconomic simulation model and a Bayesian difference‐in‐difference regression to examine the conditions under which MPAs can provide population‐level conservation benefits inside and outside their borders and to assess evidence of those benefits in the Channel Islands. As of 2017, we estimated that biomass densities of targeted fin‐fish had a median value 81% higher (90% credible interval: 23–148) inside the Channel Island MPAs than outside. However, we found no clear effect of these MPAs on mean total biomass densities at the population level: estimated median effect was –7% (90% credible interval: –31 to 23) from 2015 to 2017. Our simulation model showed that effect sizes of MPAs of

Improving estimates of the state of global fisheries depends on better data - Daniel Ovando; Ray Hilborn; Cole Monnahan; Merrill Rudd; Rishi Sharma; James T. Thorson; Yannick Rousseau; Yimin Ye (Fish and Fisheries, 2021)
Implementation of the United Nations Sustainable Development Goals requires assessments of the global state of fish populations. While we have reliable estimates of stock status for fish populations accounting for approximately half of recent global catch, our knowledge of the state of the majority of the world's “unassessed” fish stocks remains highly uncertain. Numerous publications have produced estimates of the global status of these unassessed fisheries, but limited quantity and quality of data along with methodological differences have produced counterintuitive and conflicting results. Here, we show that despite numerous efforts, our understanding of the status of global fish stocks remains incomplete, even when new sources of broadly available data are added. Estimates of fish populations based primarily on catch histories on average performed 25% better than a random guess. But, on average, these methods assigned fisheries to the wrong FAO status category 57% of the time. Within these broad summaries, the performance of models trained on our tested data sources varied widely across regions. Substantial improvements to estimates of the state of the world's exploited fish populations depend more on expanded collection of new information and efficient use of existing data than development of new modelling methods.

A Review of the Opportunities and Challenges for Using Remote Sensing for Management of Surface-Canopy Forming Kelps - Kyle C. Cavanaugh; Tom Bell; Maycira Costa; Norah E. Eddy; Lianna Gendall; Mary G. Gleason; Margot Hessing-Lewis; Rebecca Martone; Meredith McPherson; Ondine Pontier; Luba Reshitnyk; Rodrigo Beas-Luna; et al. (Frontiers in Marine Science, 2021)
Surface-canopy forming kelps provide the foundation for ecosystems that are ecologically, culturally, and economically important. However, these kelp forests are naturally dynamic systems that are also threatened by a range of global and local pressures. As a result, there is a need for tools that enable managers to reliably track changes in their distribution, abundance, and health in a timely manner. Remote sensing data availability has increased dramatically in recent years and this data represents a valuable tool for monitoring surface-canopy forming kelps. However, the choice of remote sensing data and analytic approach must be properly matched to management objectives and tailored to the physical and biological characteristics of the region of interest. This review identifies remote sensing datasets and analyses best suited to address different management needs and environmental settings using case studies from the west coast of North America. We highlight the importance of integrating different datasets and approaches to facilitate comparisons across regions and promote coordination of management strategies.

Correction to: Bacterial etiology of community-acquired pneumonia in immunocompetent hospitalized patients and appropriateness of empirical treatment recommendations: an international point-prevalence study - Manuela Carugati; S. Aliberti; G. Sotgiu; F. Blasi; A. Gori; R. Menendez; M. Encheva; M. Gallego; P. Leuschner; S. Ruiz-Buitrago; S. Battaglia; R. Fantini; et al. (European Journal of Clinical Microbiology & Infectious Diseases, 2021)

Global status of groundfish stocks - Ray Hilborn; Daniel J. Hively; Nicole Baker Loke; Carryn L. de Moor; Hiroyuki Kurota; Johannes N. Kathena; Pamela M. Mace; Cóilín Minto; Ana M. Parma; Juan‐Carlos Quiroz; Michael C. Melnychuk (Fish and Fisheries, 2021)
We review the status of groundfish stocks using published scientific assessments for 349 individual stocks constituting 90% of global groundfish catch. Overall, average stock abundance is increasing and is currently above the level that would produce maximum sustainable yield (MSY). Fishing pressure for cod‐like fishes (Gadiformes) and flatfishes (Pleuronectiformes) was, for several decades, on average well above levels associated with MSY, but is now at or below the level expected to produce MSY. In contrast, fishing pressure for rockfishes (Scorpaeniformes) decreased from near MSY‐related levels in the mid‐1990s, and since the mid‐2000s has remained on average at only one third of MSY‐related levels. Regions with the most depressed groundfish stocks are the Northwest Atlantic and the Pacific coast of South America, while stocks from the Northeast and Eastern Central Pacific, Northeast Atlantic, Southeast Atlantic and Southwest Pacific tend to have greatest average abundance relative to MSY‐based reference points. In the most recent year available for each stock, the catch was only 61% of MSY. Equilibrium yield curves indicate that 76% of global potential groundfish yield could be achieved using current estimates of fishing pressure. 15% of this is lost by excess fishing pressure, 67% results from lower than optimal fishing pressure on healthy stocks and 18% is lost from stocks currently overfished but rebuilding. Thus, there is modest opportunity to increase catch of global groundfish fisheries by reducing overfishing on some stocks, but more by increasing harvest on others. However, there may be other reasons not to fully exploit these stocks.

Was historical cisco Coregonus artedi yield consistent with contemporary recruitment and abundance in Lake Superior? - Benjamin J. Rook; Michael J. Hansen; Cory A. Goldsworthy; Bradley A. Ray; Owen T. Gorman; Daniel L. Yule; Charles R. Bronte (Fisheries Management and Ecology, 2021)
Historically, cisco Coregonus artedi Lesueur was the predominant prey fish and target of commercial fisheries throughout Lake Superior, but most spawning stocks collapsed by the mid‐1900s. Stocks partially recovered by the early 1990s, but contemporary abundance is considered to be below historical levels and driven by intermittent recruitment. Stochastic, age‐structured simulation models were used to determine whether historical (pre‐1955) cisco yield in Lake Superior was consistent with contemporary (1992–2015) abundance, life‐history characteristics and recruitment dynamics. When compared to contemporary stocks, the findings suggest historical stocks had: (1) similar recruits per spawner at low spawning stock sizes; (2) lower rates of compensatory density dependence; (3) similar or lower recruitment variation depending on the area and (4) higher median adult and age‐1 density. These findings are consistent with the hypothesis that eutrophication during the historical period supported greater recruitment and adult abundance and that re‐oligotrophication during the contemporary period may be limiting full recovery.

Comparative evaluation of machine learning models for groundwater quality assessment - Shine Bedi; Ashok Samal; Chittaranjan Ray; Daniel Snow (Environmental Monitoring and Assessment, 2020)

Bacterial etiology of community-acquired pneumonia in immunocompetent hospitalized patients and appropriateness of empirical treatment recommendations: an international point-prevalence study - Manuela Carugati; S. Aliberti; G. Sotgiu; F. Blasi; A. Gori; R. Menendez; M. Encheva; M. Gallego; P. Leuschner; S. Ruiz-Buitrago; S. Battaglia; R. Fantini; et al. (European Journal of Clinical Microbiology & Infectious Diseases, 2020)

TRY plant trait database – enhanced coverage and open access - Jens Kattge; Gerhard Bönisch; Sandra Díaz; Sandra Lavorel; Iain Colin Prentice; Paul Leadley; Susanne Tautenhahn; Gijsbert D. A. Werner; Tuomas Aakala; Mehdi Abedi; Alicia T. R. Acosta; George C. Adamidis; et al. (Global Change Biology, 2020)
Plant traits—the morphological, anatomical, physiological, biochemical and phenological characteristics of plants—determine how plants respond to environmental factors, affect other trophic levels, and influence ecosystem properties and their benefits and detriments to people. Plant trait data thus represent the basis for a vast area of research spanning from evolutionary biology, community and functional ecology, to biodiversity conservation, ecosystem and landscape management, restoration, biogeography and earth system modelling. Since its foundation in 2007, the TRY database of plant traits has grown continuously. It now provides unprecedented data coverage under an open access data policy and is the main plant trait database used by the research community worldwide. Increasingly, the TRY database also supports new frontiers of trait‐based plant research, including the identification of data gaps and the subsequent mobilization or measurement of new data. To support this development, in this article we evaluate the extent of the trait data compiled in TRY and analyse emerging patterns of data coverage and representativeness. Best species coverage is achieved for categorical traits—almost complete coverage for ‘plant growth form’. However, most traits relevant for ecology and vegetation modelling are characterized by continuous intraspecific variation and trait–environmental relationships. These traits have to be measured on individual plants in their respective environment. Despite unprecedented data coverage, we observe a humbling lack of completeness and representativeness of these continuous traits in many aspects. We, therefore, conclude that reducing data gaps and biases in the TRY database remains a key challenge and requires a coordinated approach to data mobilization and trait measurements. This can only be achieved in collaboration with other initiatives.

Transcriptomic changes in Echinochloa colona in response to treatment with the herbicide imazamox - Alice A. Wright; Rajkumar Sasidharan; Liisa Koski; Marianela Rodriguez-Carres; Daniel G. Peterson; Vijay K. Nandula; Jeffery D. Ray; Jason A. Bond; David R. Shaw (Planta, 2018)

Recent progress in the study of accessory minerals - Lutz Nasdala; Igor Broska; Daniel E. Harlov; Ray Macdonald (Mineralogy and Petrology, 2017)

Naltrexone moderates the relationship between cue-induced craving and subjective response to methamphetamine in individuals with methamphetamine use disorder - Daniel J. O. Roche; Matthew J. Worley; Kelly E. Courtney; Spencer Bujarski; Edythe D. London; Steven Shoptaw; Lara A. Ray (Psychopharmacology, 2017)

The Effect of Biomass Densification on Structural Sugar Release and Yield in Biofuel Feedstock and Feedstock Blends - Edward J. Wolfrum; Nicholas J. Nagle; Ryan M. Ness; Darren J. Peterson; Allison E. Ray; Daniel M. Stevens (BioEnergy Research, 2017)

Major cereal crops benefit from biological nitrogen fixation when inoculated with the nitrogen‐fixing bacterium Pseudomonas protegens Pf‐5 X940 - Ana Romina Fox; Gabriela Soto; Claudio Valverde; Daniela Russo; Antonio Lagares; Ángeles Zorreguieta; Karina Alleva; Cecilia Pascuan; Romina Frare; Jesús Mercado‐Blanco; Ray Dixon; Nicolás Daniel Ayub (Environmental Microbiology, 2016)
Summary A main goal of biological nitrogen fixation research has been to expand the nitrogen‐fixing ability to major cereal crops. In this work, we demonstrate the use of the efficient nitrogen‐fixing rhizobacterium Pseudomonas protegens Pf‐5 X940 as a chassis to engineer the transfer of nitrogen fixed by BNF to maize and wheat under non‐gnotobiotic conditions. Inoculation of maize and wheat with Pf‐5 X940 largely improved nitrogen content and biomass accumulation in both vegetative and reproductive tissues, and this beneficial effect was positively associated with high nitrogen fixation rates in roots. 15 N isotope dilution analysis showed that maize and wheat plants obtained substantial amounts of fixed nitrogen from the atmosphere. Pf‐5 X940‐GFP‐tagged cells were always reisolated from the maize and wheat root surface but never from the inner root tissues. Confocal laser scanning microscopy confirmed root surface colonization of Pf‐5 X940‐GFP in wheat plants, and microcolonies were mostly visualized at the junctions between epidermal root cells. Genetic analysis using biofilm formation‐related Pseudomonas mutants confirmed the relevance of bacterial root adhesion in the increase in nitrogen content, biomass accumulation and nitrogen fixation rates in wheat roots. To our knowledge, this is the first report of robust BNF in major cereal crops.

Genome-wide association of familial prostate cancer cases identifies evidence for a rare segregating haplotype at 8q24.21 - Craig C. Teerlink; Daniel Leongamornlert; Tokhir Dadaev; Alun Thomas; James Farnham; Robert A. Stephenson; Shaun Riska; Shannon K. McDonnell; Daniel J. Schaid; William J. Catalona; S. Lilly Zheng; Kathleen A. Cooney; et al. (Human Genetics, 2016)

Sub-Lethal Effects of Copper on Salmonids: An Avoidance Evaluation Using a Direct Test Method - Eric L. Van Genderen; Diana L. Dishman; W. Ray Arnold; Joseph W. Gorsuch; Daniel J. Call (Bulletin of Environmental Contamination and Toxicology, 2016)

NSDF: Neuroscience Simulation Data Format - Subhasis Ray; Chaitanya Chintaluri; Upinder S. Bhalla; Daniel K. Wójcik (Neuroinformatics, 2016)

Real‐time spatial management approaches to reduce bycatch and discards: experiences from Europe and the United States - Alyson S Little; Coby L Needle; Ray Hilborn; Daniel S Holland; C Tara Marshall (Fish and Fisheries, 2015)
Spatial management measures are currently being used to manage bycatch and discards, given the spatial heterogeneity of fish distributions. However, permanent fishing closures are often poorly implemented, unresponsive to stock dynamics and do not achieve their management objectives. Recently, real‐time spatial management tools for managing bycatch and discards implemented under either a comanagement or self‐governance approach have been introduced in Europe and the US . Real‐time catch and discard information is shared among fishers to incentivise and encourage vessels to leave areas of high bycatch. Here, the similarities and differences, in governance, implementation and management of ten real‐time spatial management systems from across Europe and the US are reviewed. A framework is developed to characterize the attributes associated with voluntary, private and regulatory real‐time spatial management tools. Challenges and management practices in the different case studies are reviewed providing insights for designing these spatial management tools. The results illustrate that real‐time spatial management approaches can create incentives for fishers to develop, use and share information and technology to avoid undesired catch. Compared with Europe, the US has developed spatial management tools with more truly real‐time mechanisms and with greater involvement of the fishing industry in designing and operating the tools.

Comparison of low-carbon pathways for California - Geoffrey M. Morrison; Sonia Yeh; Anthony R. Eggert; Christopher Yang; James H. Nelson; Jeffery B. Greenblatt; Raphael Isaac; Mark Z. Jacobson; Josiah Johnston; Daniel M. Kammen; Ana Mileva; Jack Moore; et al. (Climatic Change, 2015)

Predictors of smoking lapse in a human laboratory paradigm - Daniel J. O. Roche; Spencer Bujarski; Nathasha R. Moallem; Iris Guzman; Jenessa R. Shapiro; Lara A. Ray (Psychopharmacology, 2014)

Association analysis of 9,560 prostate cancer cases from the International Consortium of Prostate Cancer Genetics confirms the role of reported prostate cancer associated SNPs for familial disease - Craig C. Teerlink; Stephen N. Thibodeau; Shannon K. McDonnell; Daniel J. Schaid; Antje Rinckleb; Christiane Maier; Walther Vogel; Geraldine Cancel-Tassin; Christophe Egrot; Olivier Cussenot; William D. Foulkes; Graham G. Giles; et al. (Human Genetics, 2014)

Validation of prostate cancer risk-related loci identified from genome-wide association studies using family-based association analysis: evidence from the International Consortium for Prostate Cancer Genetics (ICPCG) - Guangfu Jin; Lingyi Lu; Kathleen A. Cooney; Anna M. Ray; Kimberly A. Zuhlke; Ethan M. Lange; Lisa A. Cannon-Albright; Nicola J. Camp; Craig C. Teerlink; Liesel M. FitzGerald; Janet L. Stanford; Kathleen E. Wiley; et al. (Human Genetics, 2012)

Head Impact Exposure in Youth Football - Ray W. Daniel; Steven Rowson; Stefan M. Duma (Annals of Biomedical Engineering, 2012)

Soluplus-Solubilized Citrated Camptothecin—A Potential Drug Delivery Strategy in Colon Cancer - Naveen K. Thakral; Alok R. Ray; Daniel Bar-Shalom; André Huss Eriksson; Dipak K. Majumdar (AAPS PharmSciTech, 2012)

Validation of Concussion Risk Curves for Collegiate Football Players Derived from HITS Data - James R. Funk; Steven Rowson; Ray W. Daniel; Stefan M. Duma (Annals of Biomedical Engineering, 2012)

Contrasting Global Trends in Marine Fishery Status Obtained from Catches and from Stock Assessments - TREVOR A. BRANCH; OLAF P. JENSEN; DANIEL RICARD; YIMIN YE; RAY HILBORN (Conservation Biology, 2011)
There are differences in perception of the status of fisheries around the world that may partly stem from how data on trends in catches over time have been used. On the basis of catch trends, it has been suggested that about 70% of all stocks are overexploited due to unsustainable harvesting and 30% of all stocks have collapsed to

Carbon Inputs and Water Uptake in Deep Soils of an Eastern Amazon Forest - Eric Davidson; Paul A. Lefebvre; Paulo M. Brando; David M. Ray; Susan E. Trumbore; Luis A. Solorzano; Joice N. Ferreira; Mercedes M. da C. Bustamante; Daniel C. Nepstad (Forest Science, 2011)
Rooting depth affects soil profiles of water uptake and carbon inputs. Here we explore the importance of deep roots in a mature tropical forest of eastern Amazonia, where a throughfall exclusion experiment was conducted to test the resilience of the forest to experimentally induced drought. We hypothesized that soil water depletion occurred below the depth previously measured by sensors in 11-m-deep soil pits and that only a small root biomass is necessary to affect water uptake and the isotopic signature of soil CO2. A noninvasive electrical profiling method demonstrated greater depletion of soil water in the 11-18 m depth increment in the exclusion plot compared with the control plot by the end of the 3rd year of the experiment. A fine root biomass of only 0.1 g/cm3 measured at 3-6 m was sufficient for soil water drawdown and for imparting an isotopic signature of modern soil 14CO2 in both plots. A soil 13CO2 profile indicated drought stress in the exclusion plot. Fine root inputs of organic C to deep soils are small with respect to the carbon dynamics of the forest, but the deep rooting habit clearly affects the ecosystem water balance and profiles of soil CO2.

HPMA Copolymer-Aminohexylgeldanamycin Conjugates Targeting Cell Surface Expressed GRP78 in Prostate Cancer - Nate Larson; Abhijit Ray; Alexander Malugin; Daniel B. Pike; Hamidreza Ghandehari (Pharmaceutical Research, 2010)

Natural habitat change, commercial fishing, climate, and dispersal interact to restructure an Alaskan fish metacommunity - Peter A. H. Westley; Daniel E. Schindler; Thomas P. Quinn; Gregory T. Ruggerone; Ray Hilborn (Oecologia, 2010)

Groundwater source assessment program for the state of Hawaii, USA: methodology and example application - Robert B. Whittier; Kolja Rotzoll; Sushant Dhal; Aly I. El-Kadi; Chittaranjan Ray; Daniel Chang (Hydrogeology Journal, 2010)

Treatment of an Iron-rich ARD Using Waste Carbonate Rock: Bench-Scale Reactor Test Results - Daniel Ray; Malcolm Clark; Tracey Pitman (Mine Water and the Environment, 2009)

Prevalence and type distribution of human papillomavirus in 5,000 British Columbia women—implications for vaccination - Richard A. Moore; Gina Ogilvie; Daniel Fornika; Veronika Moravan; Marc Brisson; Mahsa Amirabbasi-Beik; Anita Kollar; Thomas Burgess; Ray Hsu; Laura Towers; Jane Lo; Jasenka Matisic; et al. (Cancer Causes & Control, 2009)

Effects of partial throughfall exclusion on the phenology of Coussarea racemosa (Rubiaceae) in an east-central Amazon rainforest - Paulo Brando; David Ray; Daniel Nepstad; Gina Cardinot; Lisa M. Curran; Rafael Oliveira (Oecologia, 2006)

Dynamics of fine root carbon in Amazonian tropical ecosystems and the contribution of roots to soil respiration - Susan Trumbore; Enir Salazar Da Costa; Daniel C. Nepstad; Plínio Barbosa De Camargo; Luiz A. Martinelli; David Ray; Teresa Restom; Whendee Silver (Global Change Biology, 2006)
Radiocarbon ( 14 C) provides a measure of the mean age of carbon (C) in roots, or the time elapsed since the C making up root tissues was fixed from the atmosphere. Radiocarbon signatures of live and dead fine ( 40 years). Measurements of 14 C in the structural tissues of roots known to have grown during 2002 demonstrate that new roots are constructed from recent ( 14 C values in live roots most likely indicate the mean lifetime of the root rather than the isotopic signature of inherited C or C taken up from the soil. Estimates of the mean residence time of C in forest fine roots (inventory divided by loss rate) are substantially shorter (1–3 years) than the age of standing fine root C stocks obtained from radiocarbon (4–11 years). By assuming positively skewed distributions for root ages, we can effectively decouple the mean age of C in live fine roots (measured using 14 C) from the rate of C flow through the live root pool, and resolve these apparently disparate estimates of root C dynamics. Explaining the 14 C values in soil pore space CO 2 , in addition, requires that a portion of the decomposing roots be cycled through soil organic matter pools with decadal turnover time.

Application of the Algebraic Difference Approach for Developing Self-Referencing Specific Gravity and Biomass Equations - Lewis Jordan; Ray Souter; Bernard Parresol; Richard F. Daniels (Forest Science, 2006)
Biomass estimation is critical for looking at ecosystem processes and as a measure of stand yield. The density-integral approach allows for coincident estimation of stem profile and biomass. The algebraic difference approach (ADA) permits the derivation of dynamic or nonstatic functions. In this study we applied the ADA to develop a self-referencing specific gravity function and biomass function as part of a density-integral system composed of taper, volume, specific gravity, and biomass functions. This was compared to base systems of similar equations that did not have the self-referencing parameter specifications. Systems of equations were fit using nonlinear, seemingly unrelated regressions with nonlinear cross-equation constraints to account for contemporaneous correlations in the data. Results suggest that correct volume determination is more critical than specific gravity for accurate biomass estimates. The goodness-of-fit statistics clearly show that the self-referencing system provided a better fit than the base system.

Parsimonious and Completely Compatible Taper, Total, and Merchantable Volume Models - Lewis Jordan; Kenneth Berenhaut; Ray Souter; Richard F. Daniels (Forest Science, 2005)
A parsimonious and compatible system of taper, total, and merchantable volume equations sharing a common vector of three parameter estimates was derived from Clark and Saucier's (1990) volume ratio model. Clark and Saucier's model expresses volume inside bark as a function of outside bark diameter and is itself not compatible with the derived taper equation. To ensure compatibility, models were fit to express volume outside bark as functions of diameter outside bark. By constraining the limits of integration of the taper function to go from the tip to groundline diameter, a completely compatible system of taper, total, and merchantable volume equations were developed. Systems of equations were fit using nonlinear seemingly unrelated regressions with nonlinear cross-equation constraints to account for contemporaneous correlations in the data. The system fit was found to account for at least 96% of the variation in diameter outside bark, total, and merchantable outside bark volume. FOR. SCI. 51(6):578–584.

Fore-period effect and stop-signal reaction time - Chiang-Shan Ray Li; John H. Krystal; Daniel H. Mathalon (Experimental Brain Research, 2005)

Amazon drought and its implications for forest flammability and tree growth: a basin‐wide analysis - Daniel Nepstad; Paul Lefebvre; Urbano Lopes da Silva; Javier Tomasella; Peter Schlesinger; Luiz Solórzano; Paulo Moutinho; David Ray; José Guerreira Benito (Global Change Biology, 2004)
Severe drought in moist tropical forests provokes large carbon emissions by increasing forest flammability and tree mortality, and by suppressing tree growth. The frequency and severity of drought in the tropics may increase through stronger El Niño Southern Oscillation (ENSO) episodes, global warming, and rainfall inhibition by land use change. However, little is known about the spatial and temporal patterns of drought in moist tropical forests, and the complex relationships between patterns of drought and forest fire regimes, tree mortality, and productivity. We present a simple geographic information system soil water balance model, called RisQue (Risco de Queimada – Fire Risk) for the Amazon basin that we use to conduct an analysis of these patterns for 1996–2001. RisQue features a map of maximum plant‐available soil water (PAW max ) developed using 1565 soil texture profiles and empirical relationships between soil texture and critical soil water parameters. PAW is depleted by monthly evapotranspiration (ET) fields estimated using the Penman–Monteith equation and satellite‐derived radiation inputs and recharged by monthly rain fields estimated from 266 meteorological stations. Modeled PAW to 10 m depth (PAW 10 m ) was similar to field measurements made in two Amazon forests. During the severe drought of 2001, PAW 10 m fell to below 25% of PAW max in 31% of the region's forests and fell below 50% PAW max in half of the forests. Field measurements and experimental forest fires indicate that soil moisture depletion below 25% PAW max corresponds to a reduction in leaf area index of approximately 25%, increasing forest flammability. Hence, approximately one‐third of Amazon forests became susceptible to fire during the 2001 ENSO period. Field measurements also suggest that the ENSO drought of 2001 reduced carbon storage by approximately 0.2 Pg relative to years without severe soil moisture deficits. RisQue is sensitive to spin‐up time, rooting depth, and errors in ET estimates. Improvements in our ability to accurately model soil moisture content of Amazon forests will depend upon better understanding of forest rooting depths, which can extend to beyond 15 m. RisQue provides a tool for early detection of forest fire risk.

Avenues for increasing salt tolerance of crops, and the role of physiologically based selection traits - Rana Munns; Shazia Husain; Anna Rita Rivelli; Richard A. James; A.G. Condon; Megan P. Lindsay; Evans S. Lagudah; Daniel P. Schachtman; Ray A. Hare (Plant and Soil, 2002)

Effect of a growth hormone treatment on bone orthotropic elasticity in dwarf rats - Sean S. Kohles; Daniel A. Martinez; James R. Bowers; Arthur C. Vailas; Ray Vanderby (Annals of Biomedical Engineering, 1997)

Mechanical and biochemical analyses of tibial compartment fascia in chronic compartment syndrome - Christof Hurschler; Ray Vanderby; Daniel A. Martinez; Arthur C. Vailas; William D. Turnipseed (Annals of Biomedical Engineering, 1994)

Potato notes - C. Tice; W. C. Edmundson; Ray D. Hews; H. C. Moore; H. O. Werner; W. H. Martin; Daniel Dean; W. A. McCubbin; W. H. Zimmerly (American Journal of Potato Research, 1924)